Self-efficacy in hemodialysis patients and its related factors - Rambod, M; Peyravi, H; Sarban, M.T; Rafii, F; Hosseini, F (Advances in Nursing & Midwifery, 2009)
Background End-stage-renal-disease (ESRD) patients treated by hemodialysis require major lifestyle changes and self-efficacy in the treatment regimen to comply with their chronic illness. Clients’ perception of being self-efficient results in increased self-care activities and adherence to medical regimen. Although client’s self-efficiency can affect on outcomes of the disease, few study is available in this regard. Purpose This descriptive correlational study was carried out to identify self-efficacy of hemodialysis patients and its related factors. Methods 200 patients referring to healthcare setting affiliated with Iran Medical University were selected by convenience sampling method. A tool, Guidelines for Health Promotion, was used to assess self-efficacy in the treatment regimen. The tool was made reliable by test-retest method. Results Findings showed that self-efficacy was correlated with educational level, dialysis duration and weight difference between 2 dialysis sessions. In contrast, no correlation was found between self-efficacy and age as well as sex. Conclusion The study showed a significant relationship between self-efficacy and some personal characteristics of patients. Thus, it is necessary for nurses to assess self-efficacy of their patients. In addition, nurses are in a key position to influence on self-efficacy of their patients and improve self-care activities of them. To achieve these, they can provide necessary instructions for their clients to control stress and emotional as well as physical stimulations. Keywords: Self-efficacy, Chronic renal disease, Hemodialysis, Nursing.